2018
DOI: 10.1071/hc17084
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia associated with long-term medication use in the elderly: an analysis in general practice

Abstract: INTRODUCTION The aim of this study is to determine the prevalence of hyponatremia, its association with long-term medication use and underlying chronic conditions, the rate of hospitalisation and death within 3 months from its discovery and its management in community-dwelling older people. METHODS One year of data for ~5635 patients aged >65 years was extracted from the databases of 19 general practitioners (GPs); 2569 (45.6%) were checked for hyponatremia. RESULTS Hyponatremia occurred in 205 (8.0%) of 2569 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…Our sample had more comorbidities compared to the literature [ 19 , 31 ], as was anticipated since we only included older patients. A very high proportion of patients in our study were using angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor blockers, thiazide diuretics and furosemide, which is in line with other studies in the literature, which show that these drugs predispose patients to hyponatremia [ 35 , 36 ]; however, for some drugs, such as furosemide, this association may not reflect a causal role with hyponatremia but a causal role between the indication for which the medication is prescribed (more typically heart failure) and hyponatremia.…”
Section: Discussionsupporting
confidence: 90%
“…Our sample had more comorbidities compared to the literature [ 19 , 31 ], as was anticipated since we only included older patients. A very high proportion of patients in our study were using angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor blockers, thiazide diuretics and furosemide, which is in line with other studies in the literature, which show that these drugs predispose patients to hyponatremia [ 35 , 36 ]; however, for some drugs, such as furosemide, this association may not reflect a causal role with hyponatremia but a causal role between the indication for which the medication is prescribed (more typically heart failure) and hyponatremia.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on older patients have reported a prevalence of chronic hyponatremia of 8% among those living in private homes [ 19 ]. Tay et al measured the electrolytes of 5873 outpatients (age ≥ 60 years) and found that 403 (6.9%) had hyponatremia in at least one blood test [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant administration of drugs that affect water homeostasis, such as SSRIs, SNRIs, NSAIDs, or benzodiazepines, is frequent in older patients with thiazide-associated hyponatremia [ 5 ]. In a retrospective study of 2569 patients (aged > 65 years) in community-dwelling older people, Grattagliano et al reported the likelihood of hyponatremia trebled when four drugs were taken, and it was seven-fold higher with the use of six drugs [ 19 ]. As mentioned earlier, our study identified PPIs, loop diuretics, potassium sparing diuretics, ACEIs/ARBs, thiazide diuretics and NSAIDs as drugs frequently associated with hyponatremia in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [13][14][15][16], the exclusion criteria for the participants included conditions related to electrolyte abnormalities (such as hyponatremia). The criteria were as follows:…”
Section: Exclusion Criteriamentioning
confidence: 99%